Certain Conclusions Made by Complex Analysis of Slav Ethno Genesis - Budniak, Danuta (Respectus Philologicus, 2004)
The present paper considers the language, which the ancient Slavs used to speak. Consciousness in common is subjected to the analysis because it is related with one of the most important characteristics of the ethnos. The results gained from the complex analysis of Slav ethnogenesis are the evidence of some ancient authors to be found in written sources. The paper focuses on the following problems: language and ethnos, language and culture, language and mentality.